PENGGUNAAN MEDIA BUSY BOOK UNTUK MENINGKATKAN KEMAMPUAN BAHASA ANAK KELOMPOK B1 DI RA PANGLIMA SUDIRMAN SUMBERSEKAR DAU MALANG - Diyah Safitri; Mohammad Afifulloh; Ika Anggraheni (Jurnal Dewantara, 2019)
In learning process, a teacher must have broad potential and knowledge. Because a teacher must develop his potential to create creative and innovative learning media so that the students will be happy and they will not be bored easily. It becomes a teacher’s problem because of the lack of insight into the media that is fun for children. At the time of learning, they just imitate writing on the board, read books so it makes learning is less fun for children. The purpose of this study was to determine the improvement of languange skills by using the media busy book to the children of group B1 RA Panglima Sudirman Sumbersekar Dau. The use of the media busy book has many kinds of interesting game.         This study used qualitative approach with a type af classroom action research. Each cycle consists of four stage, they are planning, implementation, observation and reflection. The subjects of this study were 17 students of group B1 RA Panglima Sudirman Sumbersekar Dau. The object of this study is about improving language skills by using media busy book. Data collection techniques use observation, documentation, and interviewas. Data analysis techniques used data collection, data reduction and conclusions. Data validity techniques in this study by triangulating, discussing with colleagues and comparing the results of observations, documentation and interviews. The indicator of success in this study is that if a student reaches 75 percent or more so the student gets minimum criteria. The results of this study indicates an increase in language skills by using media busy book. It can be proven based on the average of language the students’ ability at pre-cycle 50,58, the number of 9 students passed. In cycle 1 the average was 33,11 with the number of 11 students passed. The average of cycle 2 was 37,29 with the number of 15 students passed. The average of students from cycle 1 to cycle 2 has increased. The percentage of completeness of the children of group B1 RA Panglima Sudirman Sumbersekar Dau.